Two cases of occupational allergic contact dermatitis from a cycloaliphatic epoxy resin in a neat oil: Case Report - Andersen Klaus E; Jensen Charlotte D (BMC, 2003)
Abstract Background Metal-working fluids contain complex mixtures of chemicals and metal workers constitute a potential risk group for the development of allergic contact dermatitis. Case presentation Two metal workers developed allergic contact dermatitis on the hands and lower arms from exposure to a neat oil used in metal processing. Patch testing revealed that the relevant contact allergen was a cycloaliphatic epoxy resin, 1,2-cyclohexanedicarboxylic acid, bis(oxiranylmethyl) ester, added to the oil as a stabilizer. None of the patients had positive reactions to the bisphenol A-based epoxy resin in the standard series. Conclusions These cases emphasize that well-known contact allergens may show up from unexpected sources of exposure. Further, it can be a long-lasting, laborious process to detect an occupational contact allergen and cooperation from the patient and the manufacturer of the sensitizing product is essential.